Gas Exchange, Water Relations and their Relationships with Photochemical Reflectance Index in Quercus ilex Plants during Water Stress and Recovery - Tsonev, Tsonko; Wahbi, Said; Sun, Pengsen; Sorrentino, Giuseppe; Centritto, Mauro (INTERNATIONAL JOURNAL OF AGRICULTURE AND BIOLOGY, 2014)
Diffusional limitations to photosynthesis (A), relative water content (RWC) and their association with photochemical reflectance index (PRI) were studied in holm oak (Quercus ilex L.) saplings subjected to water stress and subsequent water stress relief. RWC decreased sharply as drought progressed. Following rewatering, RWC gradually increased to pre-stress values. A, stomatal conductance (g(s)), mesophyll conductance (g(m)), total conductance (g(t)), and PRI changed in parallel with RWC. A decrease in A resulted from coordinated suppression in leaf conductance. As water stress progressed, A measured in non-photorespiratory conditions (A(1%O2)) became more than 3 times higher compared to that recorded at 21% \{[\}O-2], indicating that photorespiration likely increased in response to water stress. A(1%O2) was significantly correlated with all leaf conductances. A(1%O2) was limited more by g(s) than by g(m), indicating that higher g(m) favors photosynthesis over photorespiration. There was a significant linear correlation between RWC and PRI. Significant non-linear relationships were also found both between PRI and A and PRI and g(t). These data imply that PRI may clearly detect normal and stressed status of holm oak, but it is not very informative when plants are severely stressed. Overall, our data indicate that: a) PRI is an important indicator of leaf water status as evident from RWC; b) because leaf conductance did not limit photosynthesis when photorespiration was suppressed, holm oak, and in general sclerophyllous species, will respond to future elevated \{[\}CO2] significantly more than mesophyllous plants; c) PRI can be used to predict changes in the performance of holm oak subjected to physiological water stress, whereas caution is needed under severe drought. (C) 2014 Friends Science Publishers
The following values have no corresponding Zotero field: pub-location: 399-B, PEOPLES COLONY NO 1, FAISALABAD, 38090, PAKISTAN publisher: FRIENDS SCIENCE PUBL
Keywords: CO2 transport conductance; Drought; leaf gas exchange; photorespiration; Relative water content; Spectral reflectance index

Impact of the Mediterranean Urban Environment on Photosynthetic Efficiency of Quercus ilex Leaves - De Nicola, Flavia; Alfani, Anna; D’Ambrosio, Nicola (Water, Air, & Soil Pollution, 2011)
Environmental constrains and anthropogenic changes can contribute simultaneously to the limitation of plant performance in Mediterranean urban areas. Photosynthetic efficiency of Quercus ilex L. leaves from the urban area of Naples was evaluated by comparison with leaves from remote site (Vesuvius National Park). The photosynthetic performance of leaves with different age (current year [CY], 1- [1Y] and 2-year old [2Y]) was assessed by measurements of gas exchange, chlorophyll fluorescence and pigment contents. The photosynthetic activity at the urban site was higher than that at the remote site for the CY leaves, while the opposite was observed for the 1Y and 2Y leaves. The growth of Q. ilex trees was mainly sustained by the CY leaves at the urban site, whereas at the remote site the photosynthetic activity was not affected by leaf ageing. In the urban environment, Q. ilex leaves strongly decreased the photosynthetic performance with leaf ageing as highlighted by leaf gas exchanges, although the photochemistry did not show any significant change. The mature leaves of urban site drove the reductive power deriving from the photochemistry more in nonassimilative processes rather than in carbon assimilative ones, avoiding a strong decrease of PSII photochemical efficiency
Keywords: chlorophyll fluorescence; environmental stress; leaf ageing; leaf gas exchange; photosynthetic pigments; urban; urban environmental stress

Modelling leaf gas exchange in holm-oak trees in southern Spain - Infante, J. M.; Damesin, C. (Agricultural and Forest …, 1999)
This paper presents a mechanistically based C3 leaf CO2 assimilation model linked with an empirical stomatal model to simulate Quercus ilex leaf net photosynthesis and transpiration in oak-savannah ecosystems of southern Spain. The model estimates (time integration) daily and seasonal changes in carbon ®xation, transpiration, and water use ef®ciency of a single leaf in free air. Simulations were carried out on two trees for a dry year. Results shown in our study demonstrate that the modelling approach, compared to ®eld measurements, provides a realistic description of diurnal and seasonal patterns of leaf gas-exchange response to different environmental conditions, and as affected by water availability
Keywords: carbon dioxide assimilation; Drought; leaf gas exchange; oak savannah; photosynthesis model; Quercus ilex

Modelling leaf gas exchange in holm-oak trees in southern Spain - Infante, J M; Damesin, C (Agricultural and Forest …, 1999)
This paper presents a mechanistically based C3 leaf CO2 assimilation model linked with an empirical stomatal model to simulate Quercus ilex leaf net photosynthesis and transpiration in oak-savannah ecosystems of southern Spain. The model estimates (time integration) daily and seasonal changes in carbon ®xation, transpiration, and water use ef®ciency of a single leaf in free air. Simulations were carried out on two trees for a dry year. Results shown in our study demonstrate that the modelling approach, compared to ®eld measurements, provides a realistic description of diurnal and seasonal patterns of leaf gas-exchange response to different environmental conditions, and as affected by water availability
Keywords: carbon dioxide assimilation; Drought; leaf gas exchange; oak savannah; photosynthesis model; Quercus ilex

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens